Indoor Air Quality and Sick Building Syndrome in Three Selected Buildings - Norhidayah, Abdull; Lee, Chia Kuang; M. K., Azhar; S., Nurulwahida (Elsevier Ltd, 2013)
The respondents presenting with indoor environmentally associated symptoms such as sick building syndrome (SBS) are apt to have been exposed to inadequate indoor air quality (IAQ). The main objective of this study is to determine the association between IAQ parameters and symptoms of SBS in three selected buildings. The criteria of buildings selection is based on long history of occupancy and age of building. The structured questionnaire was distributed to respondents and IAQ parameters were technically measured in the selected buildings. The survey shows that the prevalence of SBS symptoms was similar in the selected buildings. Besides, no association was found between building type and SBS occurrence. IAQ parameters measurement indicated that most of the IAQ parameters were complied with the Malaysia standard of IAQ, excluded air velocity. Significant differences (p < 0.001) between the selected buildings were observed among velocity, CO2 concentration, temperature and relative humidity. However, the CO concentration (p = 0.18) and fungal counts (p = 0.83) were not significant differences between building. The findings suggested that the important predictors of sick building syndromes are ventilation and accumulation of possible contaminants within the indoor environment.